Effects of contact friction and ply blocking on the crush behaviour of thin-walled composite structures: A numerical study. (January 2023) - Liu, Haibao; Zhou, Jin; Zhang, Di; Li, Shipeng; Giannopoulos, Ioannis
Abstract: The present paper presents a three-dimensional composite damage model for predicting the crush response of thin-walled structures, i.e., cylindrical tubes, manufactured employing fibre-reinforced polymer–matrix composites. This computational model is based upon a Continuum Damage Mechanics (CDM) approach and accounts for both the intralaminar and interlaminar damage as well as nonlinear behaviour that occur in the composite materials. Experimental data, obtained from published literature, are employed to validate the proposed composite damage model. A comparison between the experimental and computationally predicted results, including the load response, energy absorption and damage morphology, shows good agreement. Subsequently, the validated computational model is employed to investigate the effects of contact friction and ply blocking on the crush response of thin-walled composite structures. The results reveal that the friction between the tube/platen surfaces has a positive effect on the crushing performance of the composite structures and the ply blocking can somehow inhibit the crushing performance of the investigated composite structures. Highlights: A composite damage model for predicting the crush response of thin-walled composite structures. Intralaminar and interlaminar damage as well as nonlinear behaviour have been accounted in this computational model. Experimental results are employed to examine the validity of the developed computational model. The validated computational model is employed to investigate the effects of contact friction and ply blocking.